Działania Samorządu Województwa Dolnośląskiego na rzecz ochotniczych straży pożarnych - Szczygieł, Zbigniew (Wydawnictwo Uniwersytetu Wrocławskiego, 2018)
Activities of the Local Government of the Lower Silesian Voivodship for the volunteer fire brigades performing rescue, training and assistance tasks. The author describes the actions based on his own experience and observations in this area.
Keywords: społeczność; ochotnicza straż pożarna; ochrona przeciwpożarowa; zadanie publiczne